Respuesta :
Answer:
Step-by-step explanation:
Y= -3x + 4..........(1)
Y= 4x - 10...........(2)
Substituting (1) into (2)
-3x + 4 = 4x - 10
-3x - 4x = -10 - 4
-7x = -14
x = -14/-7
x = 2
Putting x in (2)
y = 4(2) - 10
y = 8 - 10
y = -2
The solution of the system of equation is x = 2 and y = -2.
Given that
The system of equation is;
[tex]\rm y= -3x + 4\\\\y= 4x - 10[/tex]
We have to solve
The system of equation by substitution method.
According to the question
To determine the system of equation by substitution method following all the steps given below.
The system of equation is;
[tex]\rm y= -3x + 4\\\\y= 4x - 10[/tex]
Substitute the value of y from equation 1 to equation 2
[tex]\rm y = 4x-10\\\\-3x+4=4x-10\\\\-3x-4x=-10-4\\\\-7x=-14\\\\7x=14\\\\x = \dfrac{14}{7}\\\\x = 2[/tex]
Substitute the value of x in equation 1
[tex]\rm y = -3x+4\\\\y = -3\times 2+4\\\\y = -6+4\\\\y = -2[/tex]
Hence, the solution of the system of equation is x = 2 and y = -2.
To know more about Substitution click the link given below.
https://brainly.com/question/12895249